2009
DOI: 10.1007/s00418-009-0555-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and analysis of a truncated serotonin receptor gene expressed in neural and reproductive tissues of abalone

Abstract: In molluscs, the neurotransmitter serotonin (5-HT) has been linked to a variety of biological roles including gamete maturation and spawning. The possible involvement of 5-HT in abalone gamete release was demonstrated by a dose-dependent increase in Haliotis rubra gonad contractile bioactivity following 5-HT stimulation. Physiological functions associated with 5-HT, are mediated through binding to 5-HT receptors. A cDNA encoding a putative 5-HT receptor consisting of 359 amino acids was isolated from the tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Barbas et al (2002) described a receptor in A. californica that differed from the 5HT 1 receptor previously described by Angers et al (1998), and that more closely resembled the sequence from the 5-HT 1 receptor (5-HT 1Lym ) from Lymnaea stagnalis (Sugamori et al, 1993). Phylogenetic analyses (Mapara et al, 2008;Panasophonkul et al, 2009;Tanabe et al, 2010) indicate that additional molluscan 5-HT 1 receptors listed in Table 1 are also more closely related to 5-HT 1Lym than to the first receptor cloned from Aplysia (Angers et al, 1998), and the latter may derive from a recent gene duplication (Nagakura et al, 2010). It would be premature to delineate receptor subtypes in molluscs, and hence Greek letters were not applied and the two Aplysia receptors are distinguished by lowercase letters.…”
Section: Rnai Knockdownmentioning
confidence: 84%
“…Barbas et al (2002) described a receptor in A. californica that differed from the 5HT 1 receptor previously described by Angers et al (1998), and that more closely resembled the sequence from the 5-HT 1 receptor (5-HT 1Lym ) from Lymnaea stagnalis (Sugamori et al, 1993). Phylogenetic analyses (Mapara et al, 2008;Panasophonkul et al, 2009;Tanabe et al, 2010) indicate that additional molluscan 5-HT 1 receptors listed in Table 1 are also more closely related to 5-HT 1Lym than to the first receptor cloned from Aplysia (Angers et al, 1998), and the latter may derive from a recent gene duplication (Nagakura et al, 2010). It would be premature to delineate receptor subtypes in molluscs, and hence Greek letters were not applied and the two Aplysia receptors are distinguished by lowercase letters.…”
Section: Rnai Knockdownmentioning
confidence: 84%
“…The expression level of 5-hydroxytryptamine receptor, neuronal acetylcholine receptor, and nitric oxide synthase were found declined after metamorphosis. Serotonin and its receptors are involved in neuronal functions in mollusks, including the circadian rhythm of Aplysia californica ( Levenson et al 1999 ), locomotion of Lymnaea stagnalis ( Filla et al 2004 ), feeding of L. stagnalis ( Kawai et al 2011 ), and development of Haliotis rubra ( Panasophonkul et al 2009 ). Pharmacological and ecological experiments suggested that the 5-hydroxytryptamine receptor mediates settlement and metamorphosis of many mollusks, such as Ilyanassa obsolete ( Leise et al 2001 ) and Helisoma trivolvis ( Glebov et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gonads were embedded in paraffin and 5鈥惵祄 sections cut. Staining was performed using hematoxylin and eosin (H&E; Sigma) for histological observations, as described previously .…”
Section: Methodsmentioning
confidence: 99%